EFECTO DE LA ADICIÓN DE FLUIDO PROSTÁTICO AUTÓLOGO Y HETERÓLOGO SOBRE LA CALIDAD ESPERMÁTICA DEL SEMEN CANINO - Sánchez R., Alfonso (2013)
The effect of adding autologous or heterologous prostatic fluid in canine sperm and incubated at 38 °C (thermoresistance) on sperm motility and spermatic vigor was evaluated.Fifteen ejaculates were collected from mature English bulldog by digital manipulation.The sperm fraction and the prostatic fractions were kept separated during the collection.Prostatic fluids were processed and stored at -18 °C. An spermiogram was done for each ejaculate and then distributed in three aliquots of 0.5 ml and added 1 ml of autologous prostatic fluid, heterologous prostatic fluid or saline solution. The samples were incubated at 38 °C for 60 minutes measuring the progressive motility and spermatic vigor at 0, 15, 30,45 and 60 minutes. The results showed a lineal decreased for both parameters during the evaluation period, and without statistical difference between treatments or times of incubation. It is concluded that the progressive motility and spermatic vigor of canine semen diluted with prostatic fluid either analogous or heterologous were similar to those on saline solution.